CHARACTERIZATION OF THE HOST RESPONSE TO CLINICAL ISOLATES BELONGING TO THE STREPTOCOCCUS MILLERI GROUP - Kaiser, Julienne (My University, 2013)
The Streptococcus Milleri Group (SMG) asymptomatically colonize the gastrointestinal, female urogenital, and upper respiratory tract in the healthy population, and are therefore traditionally considered commensals. The SMG, however, are also pathogens that cause pyogenic and pulmonary infections. The factors that differentiate pathogenic from non-pathogenic isolates have proven difficult to identify, and consequently the determinants of SMG pathogenicity remain unknown. Characterization of the immune response to the SMG is important towards advancing the understanding of SMG pathogenicity, however there are limited studies that have done so.
Herein, we sought to investigate the cytokine profiles produced by human peripheral blood mononuclear cells in response to 35 clinical isolates of the SMG. Cytokine profiles varied across isolates resulting in a spectrum of responses that separated into three subgroups including a high, intermediate, and low response group. The responses were consistent across three individuals with the exception of several differences, which are discussed and warrant further studies on host susceptibility to SMG infections. The high and intermediate response groups were enriched with clinical isolates from invasive infections, which were found to induce significantly higher cytokine production than airway isolates. Cytokine induction was independent of TLR2 activation, suggesting that other pattern recognition receptors are involved in the recognition of and response to the SMG. Phenotypic characteristics, which are used in the clinical identification of the SMG, did not correlate with cytokine induction; therefore phenotypic tests are not sufficient to identify immunostimulatory isolates. The host response to the SMG characterized in this study provides foundational knowledge for future studies to investigate the mechanism of recognition as well as the function of downstream effector responses in the control of colonization and infection.
Keywords: Immunity; Immunology of Infectious Disease; Pathogenic Microbiology; Immunity